PERILAKU HIDUP BERSIH DAN SEHAT PADA SANTRI DI PONDOK PESANTREN AL-USWAH KUALA KABUPATEN LANGKAT - Shofiyyah Adilah; Putra Apriadi Siregar (CV. Adiba Aisha Amira, 2023)
Based on a preliminary study conducted by researchers at the Al-Uswah Islamic Boarding School on June 20, 2023 it was found that the facilities and facilities around the cottage can be seen that some towels were stacked on top of each other out of place, dirty clothes piled up in buckets, lots of clothes hanging inside rooms, dirty bathroom floors, dirty dishes piled up and plastic waste scattered in the wrong place. Many of the students do not wash their hands with soap with running water before eating. The purpose of this study was to determine the Implementation of Clean and Healthy Behavior in Santri at Al-Uswah Islamic Boarding School Kuala Langkat. This study aims to determine clean and healthy living behavior among santri. This research uses qualitative methods by collecting in-depth interview data. Santri have a habit of not washing their hands before eating, leaving their bed in an untidy condition. Santri assume that living in a pesantren is life as it is so they don't care about cleaning the rooms or the environment around the pesantren. Therefore, that attitude must be changed.